Pengaruh Media Sosial Terhadap Gaya Hidup Remaja Karang Taruna Di Desa Bongas - Ageng Saepudin Kanda S; Warda Anisa Maharani (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Teenagers are easily influenced by the latest trends and trends from other countries, starting from their lifestyle, way of speaking, dressing, and even their relationships. When it comes to relationships, most teenagers often abuse their lifestyle. The aim of this research is to find out how social media plays an important role in the daily lifestyle of Karang Taruna youth in Bongas Village. The method used is a descriptive qualitative method. The research results show that social media has a significant role in shaping teenagers' daily lives, with them tending to be exposed to the latest information and trends.